Mortality of Raoiella indica Hirst, 1924 (Acari: Tenuipalpidae) on in vitro action of acaricides - Santos, Jailma Rodrigues dos (2020)
Measures for the control of Raoiella indica Hirst, 1924 infesting and causing damage in Cocos nucifera crops are scarce in Brazil. In order to promote management programs of this mite in coconut tree culture, the in vitro effectiveness of abamectin, clorfenapir and phenpiroximate acaricides was compared on adult females of R. indica, according to the recommended dosage for mortality of 80% of pest mites. Mortality was evaluated after 3, 6, 12, 24, 48 and 72 hours after application, accumulated mortality and female survival analysis. Based on the normality of the data, Generalized Linear Models (GLM) and the means compared by the Tukey test at 5% probability were used. For the three parameters evaluated, abamectin was the most toxic in the first hours after application, with the highest peak mortality 6 hours later. Phenpiroximate was efficient over time, matching abamectin after 12 hours. Both caused mortality of 98% after 72 hours. The action of chlorrfenapir was later in relation to the other acaricides, however, it was the only one that caused 100% mortality. The three products were efficient in the control of R. indica in laboratory tests, however, abamectin was toxic in the first six hours after application, with efficiency of 85.42% on accumulated mortality, being the product with faster action in the control of adult females of R. indica.